Pengaruh Debat Capres dan Cawapres Pemilihan Umum 2024 Terhadap Keputusan Memilih Generasi Z Di Sulawesi Barat - Nasiruddin, Nurfadilah; Asriani, Asriani; Losi, Zainuddin; Amiruddin, Ahmad (Universitas Muhammadiyah Makassar, 2024)
The aim of this research is to determine the influence of the debate between presidential and vice presidential candidates in the 2024 general election on the decision to vote for Generation Z in West Sulawesi. The object of this research is the debate between presidential and vice presidential candidates in the 2024 presidential general election, the sampling is generation Z. The sampling technique used is nonprobability sampling. The data collection technique used in this research is a descriptive research method using survey and interview methods. The results of this research are that the debate between presidential candidates and vice presidential candidates did not completely influence generation Z's choice of voting decisions in the 2024 election. This research shows that the majority of generation Z before the debate was held had already had their choice of presidential candidate and vice presidential candidate for the reason that it was in accordance with own choice, although to a small extent influenced by watching the debate.